THE APPLICATION OF LEGAL CONSTRUCTION IN THE RULINGS OF THE CONSTITUTIONAL COURT - Bisar Bisariyadi (Fakultas Hukum Universitas Gadjah Mada, 2017)
The Constitutional Court does not only interpreting the Constitution in judicial review cases. The Courtalso applies legal construction which include constitutional construction and statutory construction. Thisarticle aims to identify this approach in the Court rulings. It also seeks to find conditions that trigger theCourt to venture on discovering the law by applying legal construction.